A broadband and low‐profile magnetoelectric dipole antenna with low radar cross section. Issue 1 (30th September 2022) - Du, Yubiao; Sun, Yurong; Guo, Weidong; Xu, Juan
Abstract: In this study, a novel broadband and low profile magnetoelectric dipole (MED) antenna with a low radar cross section (RCS) is proposed. The 10 dB RCS reduction is achieved by shifting the reflected energy to six directions, which is an efficient optimization method based on convolutional operations. Specifically, the polarization conversion metasurface (PCM) unit with high polarization conversion rate is constructed and employed in the MED antenna for RCS reduction. The proposed antenna is fabricated and measured. Measured results depict that the low RCS antenna offers good impedance matching in 12–15.6 GHz (relative bandwidth 26%). Compared with the reference antenna, the RCS of the proposed antenna is reduced by more than 10 dB from 9.9 to 16 GHz. It is proved that the proposed antenna has broadband and stable radiation performance and outstanding specular reflecting suppression capabilities.